2015
DOI: 10.1007/s13277-015-3375-5
|View full text |Cite
|
Sign up to set email alerts
|

ObRb downregulation increases breast cancer cell sensitivity to tamoxifen

Abstract: Leptin is a potent adipokine that plays an important role in the progression of breast cancer and interferes with the action of tamoxifen. We investigated the molecular mechanism underlying the effect of leptin on tamoxifen resistance in breast cancer cells that express leptin receptor (ObRb), and evaluated the impact of ObRb suppression on tamoxifen treatment in MCF-7 and tamoxifen-resistant (TAM-R) cells. Leptin-induced signaling pathway activation was examined by qRT-PCR and Western blotting. Chromatin immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…After incubation with Annexin V-FITC and propidium iodide (PI) (BD Bioscience, San Jose, CA) according to the manufacturer's recommendations [35], cell apoptosis was then analyzed using flow cytometry (FACScan; BD Biosciences) equipped with a Cell Quest software (BD Biosciences).…”
Section: Cell Lines and Culture Conditionsmentioning
confidence: 99%
“…After incubation with Annexin V-FITC and propidium iodide (PI) (BD Bioscience, San Jose, CA) according to the manufacturer's recommendations [35], cell apoptosis was then analyzed using flow cytometry (FACScan; BD Biosciences) equipped with a Cell Quest software (BD Biosciences).…”
Section: Cell Lines and Culture Conditionsmentioning
confidence: 99%
“…In relation to the above, it has been determined that leptin can influence the development of resistance to treatment with tamoxifen, an antiestrogenic drug commonly administered to breast cancer patients with the presence of ER. It was observed that combination therapy involving the blockade of the leptin receptor and treatment with tamoxifen could inhibit proliferation and promote apoptosis in breast cancer cells resistant to tamoxifen, suggesting that the suppression of leptin could be a new means to circumvent resistance to antiestrogenic treatment in breast cancer, because the signaling pathways activated by leptin could directly participate in the cellular response to the chemotherapeutic treatment 12 .…”
mentioning
confidence: 99%
“…It has been demonstrated that leptin treatment interferes with the antagonistic effects of tamoxifen in ERα-positive breast cancer cells [32,33] and the synergy between the leptin/Ob-R/STAT3 signaling pathway with the HER2 receptor induces tamoxifen resistance in breast cancer cells through differential regulation of apoptosis-related genes [35]. Interestingly, ObR knockdown significantly enhanced the inhibitory effects of tamoxifen on the proliferation and survival of tamoxifen-resistant cells [34]. We found that leptin may also have a role in AI resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, leptin is able to shape the tumor microenvironment by inducing multiple concurrent events, for example, a promotion of angiogenesis and a sustained recruitment of monocytes and macrophages, which in turn secrete VEGF (vascular endothelial growth factor) and proinflammatory cytokines [29][30][31]. However, only a few studies have indicated a role of this adipokine in endocrine resistance, such as tamoxifen resistance [26,[32][33][34][35][36][37], and so far, its involvement in AI therapy resistance has not yet been investigated. Here, we present data showing the involvement of the leptin-mediated signaling pathway in the development of AI therapy resistance, thereby suggesting how blocking leptin signaling could be further exploited for clinical utility in breast cancer resistant settings, especially for obese patients.…”
Section: Introductionmentioning
confidence: 99%